Large-eddy simulation of pulverized coal jet flame – Effect of oxygen concentration on NOx formation. (15th February 2015) - Muto, Masaya; Watanabe, Hiroaki; Kurose, Ryoichi; Komori, Satoru; Balusamy, Saravanan; Hochgreb, Simone
Highlights: Large-eddy simulation is applied to a pulverized coal flame with oxy-firing conditions. Effect of oxygen concentration on NO x formation are investigated. Peak value of the formed NO increases with increasing the O2 concentration. When equivalence ratio is larger than unity, NO decreases after its peak value. Abstract: Large-eddy simulation is applied to a laboratory-scale open-type pulverized coal flame generated by a triple stream burner, and the NO production and reduction in oxy-fuel condition are investigated for the first time. Pulverized Cerrejon coal which is classified as bituminous coal is used as a fuel. The results show that regardless of the equivalence ratio, as the O2 concentration increases from 21% to 40%, O2 consumption becomes marked because gas temperature rises and oxidation reaction is enhanced by the higher concentration of O2 . Also, NO is formed rapidly due to the oxidation reaction of nitrogen from volatile matter of coal, and its concentration reaches a few hundred ppm further downstream. After the rapid formation, in the case of equivalence ratio larger than unity, NO decreases, because the reducing atmosphere becomes dominant due to the lack of O2 . The trend becomes significant as the O2 concentration in the carrier gas increases from 21% to 40%. In the case of equivalence ratio less than unity, on the other hand, NO does not decrease clearly, because the oxidizing atmosphere contributes to the further formation of NO. Present study shows the usefulness of the large-eddy simulations for predicting the characteristics of pulverized coal flames.